Adsorption of gaseous air pollutants over Ti-doped ZGNR structures: a DFT study. (2018) - Vatsyayan, Ritwik; Singh, Rajan; Paily, Roy
In this study, we employed the density functional theory (DFT) to study the interactions between gaseous air pollutants, including di-atomic (CO and NO), tri-atomic (CO2 and HCN), and poly-atomic (HCHO and COCl2 ) species, and Ti-doped zigzag graphene nanoribbon (ZGNR) structures. During this, two types of doped structures are considered, i.e., SV-ZGNR in which Ti replaces one carbon atom and DV-ZGNR, in which Ti atom replaces two adjacent carbon atoms. All gases under consideration are observed to exhibit significant adsorption energy over doped ZGNR except COCl2 for which a catalytic dissociation is observed. Our results indicate that doped ZGNR is better for CO, NO, and HCHO adsorption as compared to that for reported doped graphene sheet. Also, DV-ZGNR is preferred over SV-ZGNR in terms of adsorption. Moreover, due to the adsorption, changes in the density of states are observed which confirms that the Ti-doped ZGNR has potential to be used as the sensing platform for these gases.